Identification and characterization of neutralization epitopes at VP2 and VP1 of enterovirus A71 - Nik Nadia, Nik Mohd Nasir; Tan, Chee Wah; Ong, Kien Chai; Sam, I-Ching; Chan, Yoke Fun (Wiley, 2018)
Enterovirus A71 (EV-A71) neutralization escape mutants were generated with monoclonal antibody MAB979 (Millipore). The VP2-T141I and VP1-D14N substitutions were identified. Using reverse genetics, infectious clones with these substitutions were constructed and tested by neutralization assay with immune sera from mice and humans. The N-terminus VP1-14 is more important than EF loop VP2-141 in acute human infection, mainly because it recognised IgM present in acute infection. The N-terminus VP1 could be a useful target for diagnostics and therapeutic antibodies in acute infection.